Enhance of Legal Protection the Health Outsourcing Workers in Health Law Number 36 of 2009 - Yohny Anwar; T. Riza Zarzani; Firman Halawa; T. M. Fauzi (Budapest International Research and Critics University, 2021)
This research is to find out and analyze the legal regulation of health services for outsourcing workers, to find out and analyze the legal protection of health for outsourcing workers and to examine and analyze the law regarding sanctions for doctors and hospitals that make mistakes in health services for workers. The writing of this thesis research methodology uses normative juridical research methods using an empirical juridical approach, with qualitative analysis. Qualitative analysis means that research results do not depend on the amount of data based on numbers, but data analyzed is carried out in-depth and holistically. The normative juridical method means that research data is analyzed according to legal norms and court decisions relating to health services for outsourced workers. Legal materials or materials used to analyze are obtained from library materials that include primary, secondary and tertiary legal materials, secondary data used as references in this study, especially those relating to the legal protection of the health of outsourced workers in the health law. Data processing is carried out by editing and making data after the data is sorted and analyzed and then interpreted logically against the applicable provisions. After that, it is presented in the form of sentence descriptions. Based on the results of the study, it is known that health services for outsourcing workers. In-Law no. 13 of 2003 concerning Manpower, which becomes the primary reference in the world of Manpower, does not find the term outsourcing. In practice, a corporate liability that violates the labour law can be legally prosecuted for companies that do not provide health insurance for workers. Hospitals and doctors who check the health conditions of workers must provide good health services for outsourced workers.